DIGITALISATION OF LOCAL GOVERNMENT ASSET MANAGEMENT: EVALUATING FIVE TECHNOLOGICAL INNOVATIONS AT THE RIAU PROVINCIAL DEPARTMENT OF ENVIRONMENT AND FORESTRY - Jingga Putri Fakar; Dedi Kusuma Habibie; Sabarno Dwirianto (Jurnal Ekonomi Manajemen Bisnis Syariah dan Teknologi, 2026)
Persistent deficiencies in public sector asset governance represent a critical challenge for regional government accountability in Indonesia, as evidenced by recurring Qualified Opinions (WDP) issued by BPK RI. This study evaluates the effectiveness of five simultaneous digital asset management innovations implemented by the Riau Province Department of Environment and Forestry (DLHK) in 2024: drone mapping with geotagging, IoT-based patrol vehicle tracking, blockchain land archive digitization, inter-UPT asset sharing via SiLADU, and RFID smart labeling for laboratory equipment. Employing a qualitative descriptive-evaluative design with an embedded case study strategy, data were collected through documentary analysis, in-depth interviews with seven key informants, and non-participant observation, analyzed using Miles et al.'s (2014) interactive model. Findings reveal that pre-innovation asset management maturity stood at 1.8 (Aware level, IAM 2015), with KIB A accuracy of 61%, 1,200-hectare cadastral discrepancy, 30% equipment utilization, and 45% vehicle downtime. Post-innovation, maturity advanced to 3.1 (Competent), KIB A accuracy reached 98.9%, equipment utilization rose to 78%, and audit opinion improved from WDP to WTP — generating positive ROI within two years from a Rp1.2 billion investment. Results confirm that integrated multi-technology deployment, underpinned by New Public Governance collaboration and ISO 55000 frameworks, constitutes a replicable institutional model for transforming public asset governance accountability.